An Analysis of the Leisure Preference System of Students with Disabilities in the Light of a Study - Laoues-Czimbalmos, Nóra; Bácsné Bába, Éva; Mező, Katalin; Kőnigh-Görögh, Dóra; Müller, Anetta Éva (International Journal of Engineering and Management Sciences, 2020)
With the increase in the number of disabled people and people with disabilities, research on the target group of people with disabilities has gained momentum in recent decades. Research is very diverse, looking at the labor market situation of people with disabilities, their leisure-time habits, or the factors that support and inhibit their sport.In our questionnaire research, the leisure and sporting habits of children with disabilities aged 8-18 are described and analyzed (N = 639). Data were processed with spss software, where basic statistics and contextual analysis were performed. The results confirm that passive activities (TV, listening to music) dominate the leisure activities of children with disabilities. Sports consumption (active and passive) was more prevalent among male respondents and less prominent among girls. In the motivation of sports, besides improving the state of health, entertainment and company appeared.